Overcoming the Revolution - E. I. Pivovar (Vestnik MGIMO-Universiteta)
A review of a recently published monograph by E.M. Kozhokin. Revolution and its overcoming. Essays on the history of the Russian mentality. Moscow, MGIMO-University, 2020, 270 s.